PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) TERHADAP KEMAMPUAN KOLABORASI PESERTA DIDIK KELAS IV SDN 06 KOTA BIMA - Amanda, Seli Tri; Anggih Tri Cahyadi; Miftahul Jannah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the Games Tournament (TGT) cooperative learning model on improving students' collaboration skills in fourth-grade science learning at SDN 06 Bima City. The problem raised is the low collaboration skills of students caused by the dominance of conventional learning methods. This study uses a quantitative approach with a pre-experimental method and a one-group pretest-posttest design. The research subjects consisted of 38 fourth-grade students. Data collection techniques were carried out through observation and collaboration ability tests. The results showed an increase in students' average scores from 75.00 in the pretest to 80.50 in the posttest. The t-test showed a significance value of 0.000 (p <0.05) which means there is a significant difference before and after using the Games Tournament (TGT) cooperative model. This indicates that the Games Tournament (TGT) cooperative model is considered Games Tournament (TGT) can be an alternative, innovative learning model that encourages active participation and develops collaboration skills in elementary school students.